Analisis Dampak Debu Dan Asap Transportasi Umum Yang Dirasakan Masyarakat Sumber Kejayan - Aminatus Sa'diah; Sudarti Sudarti (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Kejayan Sumber Kejayan is a village whose highway is connected to the provincial road. Where the provincial road is the road that is most frequently passed by public transportation, both large ones such as trailer trucks, containers, tanks and so on as well as small ones such as motorcycles, public transportation, tricycles, private cars and so on. Modern transportation as it is today, the development of transportation is increasingly rapid, which causes air pollution to also increase, this is due to the faster transportation it will require quite a lot of fuel which will result in exhaust gas or road dust also increasing caused by public transportation. The purpose of this research analysis is to determine the impact felt by the local community, especially those who live on the edge of the highway, on dust and smoke caused by public transportation. The data used are primary data and secondary data with descriptive observation method. The primary data was obtained from interviews and questionnaires with 30 local people (respondents) and secondary data was obtained from literature studies such as journals, articles, e-books and searching for data on the internet. The analysis used is descriptive analysis to identify the impact of dust and smoke on public transportation felt by local people in roadside areas. The results of the analysis show that the impact felt by the people who live or work on the edge of the highway on average experience health problems such as coughing, respiratory tract disorders, eye irritation, skin irritation (itching) or redness, headache, nausea, visual disturbances, chest pain, hypertension and also impaired smell.